Physic-chemical evaluation of leach and water from the Borba Gato streamlet within the catchment area of the urban waste landfill of Maringá, Paraná State, Brazil - doi: 10.4025/actascitechnol.v34i1.6771 - Borges, Marta Eliane Echeverria; Barros Júnior, Carlos (Acta Scientiarum. Technology, 2011)
The physic-chemical characteristics of leach deposited in the landfill waste pond and of water from the Borba Gato streamlet are evaluated. Twenty-six physic-chemical parameters were analyzed from three collection sites, or rather, two in the streamlet, one upstream (P-01) and one downstream (P-02) of the landfill waste pond, and one in the leach deposit pond (P-03). The streamlet area under analysis was impacted due to being in an agricultural area and for its urban waste deposits. Parameter concentrations of aluminum, iron and mercury were reported above the quality standard of freshwater, according to Conama 357/2005 resolution (class 2). Further, throughout the rainy period, the ammoniac nitrogen content was above the resolution quality standard for fresh water. Moreover, landfill leach was above standards of effluent discharge established by Conama 357/2005. An efficient treatment for the effluent generated in Maringá is required since there is evidence of leach pollution of the Borba Gato streamlet.